Educational tool for design and implementation of an autonomous mobile robot - (:unkn) unknown (My University, 2009)
In engineering education, the theory presented in lectures must be supported by experimental exercises. Such exercises can be implemented using educational tools. In this study, an educational tool is presented to teach advanced control processing of an autonomous mobile robot to both undergraduate and graduate students in electrical and computer engineering. Using this educational tool, engineering students can learn many fundamental aspects of control processes and image processing and develop RF communication algorithms by using micro controllers in a practical way. The tool has a flexible structure and a user-friendly graphical interface. The simulator improves collaborative study, which provides more flexibility for the students performing the laboratory experiments. The developed animation software is able to create or modify various algorithms in control. This enables students to practice and interpret the controllers via drawing conclusions by changing the parameters of the fuzzy logic controller (FLC). Students' feedback indicated that theory in lectures on control systems and robotic were only appreciated after the laboratory exercises. © 2009 TEMPUS Publications.
Keywords: Collaborating learning; Control systems and robotic education; Educational tool; Mobile robot